Fly ash-slag interaction during alkaline activation: Influence of activators on phase assemblage and microstructure formation. (30th September 2016) - Ye, Hailong; Radlińska, Aleksandra
Highlights: Interaction between slag and fly ash during activation and geopolymerization. SEM/EDS and XRD elucidate the nanostructure, phase assemblage, and compositions. Rietveld semi-quantitative analysis quantifies phase assemblage in binary system. Ternary phase diagrams with statistical composition distributions were analyzed. Abstract: In this work, the influence of activator on the interaction mechanisms between slag and low-calcium fly ash (FA-F) during alkaline activation was investigated. In particular, the evolution of phase assemblage and microstructure of alkali-activated binary slag and FA-F paste was monitored by means of X-ray diffraction with Rietveld analysis, scanning electron microscopy, and energy-dispersive spectroscopy (SEM/EDS). The results show that the nature of amorphous gels and type of crystalline phases formed are dependent on sample age, initial slag to FA-F ratio, and activator type and dosage. The interaction between FA-F and slag during alkaline activation or geopolymerization is primary demonstrated as: (1) modified nanostructure (e.g. crystallology and lattice parameters) and chemical composition of precipitates, (2) depressing or triggering the formation of some crystalline phases, and (3) spatial heterogeneity of composition in microstructure. The activator is chemically incorporated into interactions between slag and FA-F, and likely affects the dissolution and reaction kinetics.